2021
DOI: 10.3390/ijms23010429
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of miR-29a and ADAM12 Reduces Post-Ischemic Skeletal Muscle Injury and Improves Perfusion Recovery and Skeletal Muscle Function in a Mouse Model of Type 2 Diabetes and Peripheral Artery Disease

Abstract: Both Type 1 diabetes mellitus (DM1) and type 2 diabetes mellitus (DM2) are associated with an increased risk of limb amputation in peripheral arterial disease (PAD). How diabetes contributes to poor PAD outcomes is poorly understood but may occur through different mechanisms in DM1 and DM2. Previously, we identified a disintegrin and metalloproteinase gene 12 (ADAM12) as a key genetic modifier of post-ischemic perfusion recovery. In an experimental PAD, we showed that ADAM12 is regulated by miR-29a and this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…In an experimental model of limb ischemia in diabetic mice, inhibiting miRNA-29a upregulated the expression of the ADAM12 gene, coding for the disintegrin and metalloproteinase domain-containing protein 12, which improved perfusion recovery [ 119 ]. In mice with glucose intolerance, after inducing hind limb ischemia, administration of unacylated ghrelin upregulated miRNA-126, decreasing the level of VCAM-1 and the number of infiltrating inflammatory cells in ischemic muscle, potentially rescuing ischemic muscle from necrosis [ 120 ].…”
Section: Micro Rnas and Padmentioning
confidence: 99%
“…In an experimental model of limb ischemia in diabetic mice, inhibiting miRNA-29a upregulated the expression of the ADAM12 gene, coding for the disintegrin and metalloproteinase domain-containing protein 12, which improved perfusion recovery [ 119 ]. In mice with glucose intolerance, after inducing hind limb ischemia, administration of unacylated ghrelin upregulated miRNA-126, decreasing the level of VCAM-1 and the number of infiltrating inflammatory cells in ischemic muscle, potentially rescuing ischemic muscle from necrosis [ 120 ].…”
Section: Micro Rnas and Padmentioning
confidence: 99%
“…The use of mouse models and ex vivo studies have provided the tools to better understand the effects of ischemia on the skeletal muscle. The alignment of nuclei in the center of myofibers is a diagnostic feature of centronuclear myopathy, however, in the context of injury, it is a transitionary process of re-localization during repair Accordingly, we also have observed that centralized nuclei in the cross sections of myofibers of ischemic limbs of DM mice persist much longer and are present in higher numbers of fibers than in sections from control non-diabetic ischemic limbs ( 64 ).…”
Section: Adaptations Associated With Padmentioning
confidence: 71%
“…These findings suggest that despite the adequate post-HLI adaptation and recovery of C57BL/6 mice, high fat diet or hyperglycemia (HFD + STZ, or Akita mice) alters the expression of a key molecule involved in post-injury repair of limb tissue. Interestingly the ischemic hind limb skeletal muscles of diabetic C57BL/6J mice showed significantly lower expression of two genes mapped on Lsq-1 locus, i.e., BAG3 and ADAM12, compared to that in non-diabetic mouse limbs (64,68). Exogenous expression of BAG3 in the limbs of diabetic mice prior to HLI significantly reduced limb loss, improved perfusion recovery and decreased extent of skeletal muscle injury (68).…”
Section: Micrornas In Diabetic Padmentioning
confidence: 96%
“…The elucidation of the molecular mechanisms regulating the pathological conditions responsible for the development of diseases could provide valuable information that could be useful in developing new methods for the management of these diseases. Many recent studies have shown that miRNAs are promising targets for the diagnosis and treatment of various conditions, including LEAD [ 49 , 50 , 51 , 52 , 53 , 54 ], AAA [ 28 , 55 , 56 , 57 ], and CVD [ 58 , 59 ]. In particular, many investigations were carried out to evaluate the utility of proangiogenic properties of miRNAs in the therapy of peripheral atherosclerosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%